The Acquisition of Professional Social Work Competencies. - Vitali, Sharon (Social Work Education, 2011)
A three-year longitudinal cohort study followed one cohort of undergraduate social work students (n = 38) from induction to graduation, measuring and tracking the acquisition of the National Occupational Standards for Social Work. An efficient 'user-friendly' set of mixed methods was embedded within the usual programme audit process. It is proposed that this methodology can be adopted by any competency-based educational programme seeking to ensure and improve the outcomes of their curriculum, as well as being used by students and practice educators to discuss their perspectives on the student's progress. Repeated measures t-tests demonstrated that student self-rating ('ipsative') measurement can track and quantify the acquisition of student competencies. However, ipsative measurement was not significantly correlated with 'external' tutors' and practice educators' (fieldwork supervisors') ratings or with final degree gradings. This raises questions around the validity and inter-rater reliability of ipsative measurement instruments used to evaluate student performance. Ratings of interviews in the first semester made by Voices of Experience (service users) were correlated with placement marks and final degree grades.